Expand the internet access in an urban park using a WiFi offloading technique - Hernandez, Leonel; Carbono, Jair; Cantillo, Andres (Association for Scientific Computing Electrical and Engineering, 2019)
Nowadays, smart devices have grown exponentially, so they have become a necessity rather than a luxury, therefore staying connected to the Internet has facilitated people to explore national and international news, make payments for services public, virtual shopping, scheduling medical appointments, among others. Now all this demand increases every day at excessive levels and adding the robust applications that are currently being developed and launched on the market. Regarding this, it is known that currently, the internet service providers of the municipality of Soledad Atlantico do not have the physical infrastructure to maintain the availability of the service. This is where the project design of the Wi-Fi-Offloading solution to extend the coverage and the transmission of data from the cellular network, through the wireless network in the Muvdi park of the Municipality of Soledad Atlantico, is carried out with the aim of providing a solution and alternative so that the internet connection service remains available without import the data network to which you have access. The research methodology used for the development of the project is descriptive. The research design is qualitative, transactional, and non experimental. At this moment, it is in a descriptive stage, carrying out tests, and then moving on to the applied stage.